Go Green Cycling, campus-greening initiative - Mimi Rabita, Abdul Wahit (2021)
PEKAN, 24 October 2021 - The Go Green Cycling Programme with the Chairman of the Board of Directors of Universiti Malaysia Pahang (UMP) organised by Yayasan UMP recently demonstrated the importance of healthcare through cycling activities on campus and as the best practice in an effort to support the campus-greening agenda.